The Algerian community in France and its fighting role in favor of patriotism: The demonstrations of October 17, 1961 in Paris as a model. - khelifi, abdelkader (The Algerian Historical Journal, 2026)
This article deals with the study and analysis of the demonstrations of October 1961 in Paris, as it was considered a major station in the contributions of the Algerian community in the Diaspora in favor of supporting the liberation revolution. The interrogation of the memory and the sifting of the literature that dealt with this station led to the disclosure of the fact that the French state apparatus was completely complicit in the perpetration of systematic racist repression and the attempt to obliterate the crime. Presenting a civilized image of the Algerian to the French and international public opinion, and making the government of General de Gaulle, reluctant to favor the option of resuming negotiations with the representatives of the revolution.